Immunoexpression of CD34, CD117, and p53 in Hypocellular Bone Marrow Disorders - Sharma, Pooja; Palta, Anshu; Tahlan, Anita; Kaur, Manveen; Singh, Ram (Journal of Laboratory Physicians, 2021)
Objectives Hypocellular bone marrow (BM) disorders comprise heterogeneous entities associated with peripheral cytopenias and decreased production of hematopoietic cells in BM. This study was undertaken to analyze immunohistochemical expression of CD34, CD117, and p53 in morphologically diagnosed patients of hypocellular BM (aplastic anemia [AA], hypocellular myelodysplastic syndrome [h-MDS], and hypocellular acute myeloid leukemia [h-AML]).Materials and Methods BM specimens were obtained from patients presenting with pancytopenia/bicytopenia. On 30 patients diagnosed as hypocellular BM, immunohistochemistry (IHC) for CD34, CD117, and p53 was performed.Results BM cellularity was < 30% in all (100%) patients. Blast count was increased in h-MDS and h-AML. Features of dysplasia were noted in six (20%) patients. Out of these, three patients were diagnosed as h-MDS having bilineage/trilineage dysplasia, and the other three patients were of AA (11.5% patients) displaying only dyserythropoiesis. On IHC, percentage of BM CD34+ cells was increased in h-MDS+ h-AML (3.87 ± 0.86) as compared with AA (0.19 ± 0.15) and controls (0.81 ± 0.21), p = 0.01. Percentage of BM p53+ cells was also increased in h-MDS+ h-AML (2.9 ± 2.07) as compared with AA and controls, which did not show any p53+ cells, p = 0.0. No statistically significant difference was observed in the expression of CD117 in h-MDS+ h-AML (4.95 ± 3.40) compared with AA (4.49 ± 1.07), p = 0.99.Conclusion The study demonstrates the usefulness of CD34 and p53 immunoexpression as an important ancillary method in distinguishing various hypocellular BM disorders, especially h-MDS and AA. However, the role of CD117 remains unclear and needs to be evaluated further by larger studies.
Keywords: aplastic anemia; hypocellular marrow; myelodysplastic syndrome; CD34; CD117; p53